Адміністративна реформа як різновид правової реформи - Трачук, П. А.; Trachuk, P. (My University, 2010)
The article is devoted to the problem of administrative reform legalities, its main components and directions. The author analyzes the administrative territorial state system and gives some propositions to some administrative reform defects avoiding.
Трачук П. А. Адміністративна реформа як різновид правової реформи / П. А. Трачук // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 85-90.
Keywords: адміністративна реформа; правова реформа; правова природа адміністративної реформи; административная реформа; правовая реформа; правовая природа административной реформы; особенности административно-территориального устройства государства; особливості адміністративно-теріторіального устрою держави; administrative reform; legal reform; the legal nature of administrative reform; especially the administrative-territorial structure of the state